Oppida prerromanos en la orilla norte del Fretum Herculeum - Iván García Jiménez (Pallas, 2010)
This study deals with the issue of the location of the preroman oppida at the southernmost point of the province of Cadix. Although the antique literary sources have supplied us with their names and geographic indications, their exact location before the arrival of the Romans remains a controversial issue. Those sources refer to coastal settlements which, in the imperial days, fit a strictly Roman pattern but are likely to be the result of transfers of populations who moved to the sea coast while keeping their preroman names. Such is at least the hypothesis we present regarding Mellaria, Bailo and Baesippo, hoping that archeological works will provide us in the future with elements that answer that question.